Saúde Mental e pandemia da Covid-19: focalizando a perspectiva de adolescentes estudantes de uma escola pública - Cardoso, Maria Angelica Mangino (Universidade Federal de São Carlos, 2023)
Studies have pointed out that adolescence tends to be more vulnerable to the experience of psychological distress, which has been intensified by epidemiological studies carried out in the context of the Covid-19 pandemic, which indicate an increase in the rates of psychic suffering in this population. However, many times, the production of knowledge in the field of Mental Health tends to emphasize the identification of psychiatric symptoms and diagnoses in this phase of development without considering the complexity of the interrelation between social, cultural and contextual factors that surround the experience and subjectivity of the teenage people. In this way, carrying out studies and practices that allow listening to adolescents and considering their voices regarding their own experience and possibilities of care can contribute to the debate and propositions of policies and interventions that are more effective. In this direction, the objective of this research was to explore and analyze with adolescents how their mental health was in the context of the Covid-19 pandemic, as well as the care strategies used in that scenario. A qualitative research was carried out. Participants were ten female adolescents, students of a state public school, located in a socially vulnerable territory in a city in the interior of the state of São Paulo. Data production took place in person at the school, from five meetings, in which awareness and communication strategies were used, and verbal and non-verbal activities were carried out, including those present in the daily lives of the participants and the school, such as: artistic activities, writing, cutting and collages, drawings and conversation circles. The results revealed that, for the participants, mental health is related to “feeling good” and performing activities that give them pleasure, such as listening to music, drawing, watching movie series, reading, among others. In addition, they highlight the negative impacts of the pandemic on their mental health, which translates into impairments in socialization, in carrying out meaningful day-to-day activities, in school performance and in their relationship with school, concerns with themselves and with people relationships and family conflicts. Some participants also reported the need to use psychotropic medications and psychotherapy. Still as a result of the study, it is pointed out that the participants suggested that the possibility of carrying out activities in the school environment aimed at promoting mental health, such as conversation circles and carrying out group activities (watching movies, playing games, cooking) could be beneficial. The results produced demonstrated an expanded understanding of mental health, beyond symptoms and mental disorders, which dialogues with data from the literature on mental health and psychosocial care for children and adolescents. It was also possible to verify the familiarity with the theme, which leads to a debate on the medicalization of life and adolescence, as well as identifying, with the participants themselves, clues that can subsidize the development of care and health promotion strategies of this population that are more participative and contextualized to their needs.
Mental Health and Covid-19 pandemic: focusing on the perspective of adolescent students of a public school
Keywords: Adolescência; Saúde Mental; Pandemia da Covid-19; Terapia Ocupacional; Adolescence; Mental Health; COVID-19 Pandemic; Occupational Therapy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL